2017
DOI: 10.1371/journal.pone.0168582
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Antihypertensive Agents for Adult Diabetic Patients with Microalbuminuric Kidney Disease: A Network Meta-Analysis

Abstract: BackgroundAntihypertensive treatment mitigates the progression of chronic kidney disease. Here, we comparatively assessed the effects of antihypertensive agents in normotensive and hypertensive diabetic patients with microalbuminuric kidney disease.MethodsMEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials were systematically searched for randomized controlled trials (RCTs) comparing oral antihypertensive agents in adult diabetic patients with microalbuminuria. The primary efficacy outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
2
9
0
1
Order By: Relevance
“…However, the proportion of diabetic patients in that systematic review was low. Finally, a recent network meta-analysis comparing the effects of antihypertensive agents in diabetic patients with kidney disease showed that the ACEI-CCB combination therapy of fosinopril and amlodipine appeared to be the most efficacious in reducing proteinuria [28]. While the ACEI-ARB combination was not recommended due to safety concerns [6, 7], based on the results of the network meta-analysis, a combination of ACEIs or ARBs with other antihypertensive agents may deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of diabetic patients in that systematic review was low. Finally, a recent network meta-analysis comparing the effects of antihypertensive agents in diabetic patients with kidney disease showed that the ACEI-CCB combination therapy of fosinopril and amlodipine appeared to be the most efficacious in reducing proteinuria [28]. While the ACEI-ARB combination was not recommended due to safety concerns [6, 7], based on the results of the network meta-analysis, a combination of ACEIs or ARBs with other antihypertensive agents may deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous network meta-analysis (Huang et al, 2017) found that the combination therapy of trandolapril plus candesartan was the best one to reduce albuminuria in normotensive diabetic patients. However, Mann et al (2008) also mentioned that the combination therapy of ACEI and ARB reduced proteinuria to a greater extent but had less renal benefit in diabetic patients.…”
Section: Discussionmentioning
confidence: 97%
“…What should be recommended for more proteinuria reduction and less blood pressure reduction in normotensive patients with CKD? A recent network meta-analysis by Huang et al (2017) reported that the ACEI-ARB combination therapy of trandolapril+candesartan was the most efficacious in reducing albuminuria for normotensive diabetic patients. The study only included the diabetic patients, which means that the results cannot be generalized to normotensive patients with other kinds of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…In randomized controlled trials (RCTs), treatment with ACE inhibitors can slow down the decline in glomerular filtration rate (GFR) [ 5 ] and the progression to end-stage renal failure [ 6 ], independent of the reduction in blood pressure [ 5 ]. Network meta-analysis of RCTs comparing different classes of antihypertensives suggests that the ACE inhibitor-CCB combination therapy is the most efficacious therapy in reducing albuminuria in patients with diabetes and microalbuminuric kidney disease [ 7 ], while whether the findings can be generalized to people without these comorbidities is unclear. Given the limited number of often small-scale RCTs, current evidence may not be sufficient to support the use of ACE inhibitors as the first-line antihypertensive drug [ 8 ].…”
Section: Introductionmentioning
confidence: 99%